OPTIMALISASI PEMANFAATAN SAMPAH ANORGANIK MELALUI PENCIPTAAN TAMAN DESA BAGI MASYARAKAT DESA MEDALEM - Ahmad Bashri; Diky Wahyudinul; Eka Faradila; Elsa Amalia; Farica Shafa; Izzah Nor (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2022)
The purpose of community service is to increase public awareness about the importance of using plastic bottle waste. The method of implementing the Plastic Bottle Waste Utilization program as TOGA Planting Media through Community Service activities which was carried out during May 2022. Before carrying out activities, it is necessary to plan activities to be carried out to realize the program according to the planned achievement targets. The stages of the method of implementing these activities include the stages of preparation, implementation, and evaluation. The result of this program is a village park. The Village Park in Medalem is a small-scale public park that contains a few ornamental plants and Family Medicinal Plants placed on wooden shelves. Based on the results of the questionnaire, the use of plastic bottle waste is needed by the community, and the use of plastic bottle waste is also beneficial for the environment in Medalem Village. The community stated that recycling plastic bottle waste is also necessary and the community also stated that recycling plastic bottle waste is also an effective alternative for processing waste and the people of Medalem Village has been able to recycling plastic bottle waste.